PORTADA, EDITORIAL REVISTA CSSN VOL 12 - NUM 2 - Pucuna, Saul Yasaca (La Ciencia al Servicio de la Salud y la Nutrición; Vol. 12 Núm. 2 (2021): Julio 2021 - Diciembre 2021DO - 10.47244/cssn.Vol12.Iss2.661, 2022)
Portada